2022
DOI: 10.1085/jgp.202213244
|View full text |Cite
|
Sign up to set email alerts
|

Excitation–contraction coupling in cardiac, skeletal, and smooth muscle

Abstract: This work is part of a special issue on excitation-contraction coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Impaired intracellular calcium release via the modulation of intracellular calcium release channels, such as RyRs 1 and 3 and a set of related calcium (Ca 2+ )-binding proteins from the specialized intracellular calcium, store longitudinal sarco(endo)plasmic reticulum cisternae required for excitation-contraction coupling [ 30 ] in muscle by calsequestrins (CASQ) and other calcium binding proteins is a contributing factor in striated muscle health and disease [ 31 ], including clinical muscle fatigue [ 32 ]. Altered calcium signaling key protein levels following SDM spaceflight found in this work thus highlights maladaptation of the mostly slow-twitched muscle fiber (type I) containing SOL (expressing both CASQ1 and 2) where an increase in CASQ1 and CASQ2 and two other related proteins (ANXA2, ATP2A1) was detected at variance in both SDM and LDM samples, suggesting (Ca 2+ )-binding proteins as a protein hub to acute microgravity exposition of human muscle (SOL) in spaceflight.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired intracellular calcium release via the modulation of intracellular calcium release channels, such as RyRs 1 and 3 and a set of related calcium (Ca 2+ )-binding proteins from the specialized intracellular calcium, store longitudinal sarco(endo)plasmic reticulum cisternae required for excitation-contraction coupling [ 30 ] in muscle by calsequestrins (CASQ) and other calcium binding proteins is a contributing factor in striated muscle health and disease [ 31 ], including clinical muscle fatigue [ 32 ]. Altered calcium signaling key protein levels following SDM spaceflight found in this work thus highlights maladaptation of the mostly slow-twitched muscle fiber (type I) containing SOL (expressing both CASQ1 and 2) where an increase in CASQ1 and CASQ2 and two other related proteins (ANXA2, ATP2A1) was detected at variance in both SDM and LDM samples, suggesting (Ca 2+ )-binding proteins as a protein hub to acute microgravity exposition of human muscle (SOL) in spaceflight.…”
Section: Discussionmentioning
confidence: 99%
“…Since these toxins induce a synchronous pattern of muscle damage, they have become useful tools for studying the cellular processes involved in skeletal muscle degeneration and regeneration (Harris and Cullen 1990 ; Harris 2003 ). In particular, myotoxic PLA 2 s and PLA 2 homologs from the venoms of the species Bothrops asper (family Viperidae, group II secreted PLA 2 s) and Notechis scutatus (family Elapidae, group I secreted PLA 2 s) have been extensively used in these investigations, although studies with other similar toxins have been also carried out (Dixon and Harris 1996 ; Gutierrez and Ownby 2003 ; Lomonte 2023 ). Some of these myotoxins are catalytically-active Asp-49 enzymes that cleave the sn -2 ester bond in phospholipids, while PLA 2 homologs (also referred to as PLA 2 -like myotoxins) display mutations in residue 49 and other residues of the so-called calcium-binding loop, thus rendering these proteins enzymatically inactive, although keeping the ability to damage muscle fibers (Francis et al 1991 ; Ward et al 2002 ; Gutierrez and Ownby 2003 ; Lomonte and Rangel 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action of myotoxic PLA 2 s and PLA 2 homologs has been investigated by using a variety of experimental models (rodent in vivo tests, ex vivo muscle preparations and isolated cells, intravital microscopy, cell culture models, and phospholipid vesicles) (Dixon and Harris 1996 ; Gutierrez and Ownby 2003 ; Lomonte 2023 ). These investigations have shown that the first stage in the action of these toxins is the binding to the skeletal muscle plasma membrane, followed by the disruption of the integrity of muscle sarcolemma, either by enzymatic degradation of phospholipids or by a catalytically-independent destabilization of the membrane (Dixon and Harris 1996 ; Fernandez et al 2013 ; Fernandes et al 2014 ). The identity of the membrane receptors for these toxins remains largely unknown, although some candidates have been proposed (reviewed in Lomonte and Križaj ( 2021 )).…”
Section: Introductionmentioning
confidence: 99%
“…The process where skeletal muscle excitation, arriving in the form of an action potential initiated by moto neuron firing, is translated to a cytoplasmic Ca 2+ signal that activates muscle contraction is termed excitation–contraction coupling (ECC) [ 23 , 24 , 25 ]. Altered ECC function results in a modified supply of Ca 2+ ions to the contractile elements (directly, or indirectly, e.g., through mitochondrial influences), thus it has an impact on muscle performance overall.…”
Section: Introductionmentioning
confidence: 99%